Implementation of Safety Management System at Halim Perdana Kusuma Airport During the COVID-19 Pandemic - Raditya Damaris Wahyudiharto; Irfa Arzacky; Didik Sulistyo (CV. Rayyan Dwi Bharata, 2025)
QISTINA: This study examines how the Safety Management System (SMS) at Halim Perdana Kusuma Airport was used during the COVID-19 pandemic. It did this by reading journals, news, and data from the Statistics Center. The results of the study showed that the following things supported the use of SMS and personnel responses on how effectively it was used in the airport environment during the pandemic: PT. Angkasa Pura II and the Director General of Air Transportation collaborated on a number of work programs that resulted in the successful establishment of vaccination centers and checkpoints, the procurement of personal protective equipment (PPE), the acquisition of the PeduliLindungi application, and the prevention and slowing down of the virus's spread.